Impact of the Russia–Ukraine War on Women, Children, and Vulnerable Communities - Kumar, Virender (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Russia–Ukraine War, which began in February 2022, has precipitated a profound humanitarian crisis with severe and disproportionate impacts on women, children, and other vulnerable communities. By early 2025, approximately 10.6 million people have been displaced, including 6.9 million refugees and 3.7 million internally displaced persons (IDPs), intensifying pre-existing social, economic, and structural inequalities. Women, constituting 76% of refugees and 72% of the unemployed, face heightened risks of gender-based violence, human trafficking, and expanded caregiving responsibilities, while simultaneously contributing to nearly half of new businesses established amid the conflict. Children have endured catastrophic consequences, with over 2,500 killed or injured, 19,500 forcibly transferred to occupied territories, and 3,790 schools damaged, resulting in significant educational disruption, psychological trauma, and long-term developmental risks. Elderly populations and persons with disabilities (PwDs) experience compounded vulnerabilities, including restricted mobility, inadequate access to healthcare and evacuation facilities, and elevated mortality rates, while marginalized communities such as the Roma face systemic discrimination and limited humanitarian support. Widespread destruction of infrastructure, including over 2.5 million homes and 1,500 attacks on healthcare facilities, has exacerbated poverty, pushing an additional 7.1 million people below the poverty line and raising the national poverty rate from 5.5% to 24.1% in 2022. This study highlights the urgent need for gender-responsive, child-centered, and inclusive humanitarian interventions that address immediate protection, psychosocial support, and long-term recovery for those most affected by the conflict.